Taming Wicked Problems: The Role of Framing in the Construction of Corporate Social Responsibility - Reinecke, Juliane; Ansari, Shaz (Journal of Management Studies, 2016)
ABSTRACTWhile scholars have explained how business has increasingly taken on regulatory roles to address social and environmental challenges, less attention has been given to the process of how business is made responsible for wicked problems. Drawing on a study of ‘conflict minerals’ in the Democratic Republic of Congo, we examine the process through which companies became responsible for a humanitarian crisis. We contribute by: (1) bridging insights from contentious performance and deliberative approaches – to present a model of corporate political responsibilization for a wicked problem that explains how a ‘field frame’ of responsibility can emerge; (2) explaining shifting boundaries between public and private responsibilities and the changing role of the state as catalytic rather than coercive; and (3) showing how responsibility can be attributed to a target by framing an issue and its root cause in ways that allow such an attribution, and how the attribution can diffuse and solidify.